KONSEP KETAATAN KEPADA ULU AL-AMR : Analisis Hadis Riwayat Bukhari No. 7056 dan Hadis Riwayat Muslim No. 1709 - Zulkifli (DIRAYAH : Jurnal Ilmu Hadis, 2023)
Leadership is a mandatory goal in each interpretation.obedience to the leader has not been stood alone, but one frame with the obedience to God and His Messenger, in which countains two terms, namely obedience to the commandment of God and obedience to the ordinance of His Massenger (Rasulullah). Obedience to the leadership has two connontations fungctional concept. The two concept are; first ulu al-amr as the holders of pilitical power and Moslems as an onject of pilitical power.The obedient concern to the leadership in this verse ia absolute, as leadership does not intruct the forbidden by Allah. This research is library research with analytical-descriptive analysis. The primary sources in this research are the Sahih Bukhari book and the Sahih Muslim book, while the secondary sources are sharia books, books, journals and articles related to the discussion.